2020
DOI: 10.1111/ene.14458
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events are associated with the risk of multiple sclerosis

Abstract: Background and purpose Unexpected stressful life events may alter immune function and affect susceptibility to autoimmune diseases including multiple sclerosis (MS). Current results from epidemiological investigations examining the role of stress in MS remain inconsistent. The aim was to conduct the hitherto largest population‐based case–control study on this topic. Methods Extensive questionnaire information collected on lifestyle environmental factors available for 2930 incident MS cases and 6170 controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Stressful life circumstances might explain the timing of symptom exacerbation for some patients with MS, perhaps by perturbing an already unstable neuroimmunological system [237]. Sickness, accidents or death of a family member and major changes to a romantic or working relationship posed a 14% to 26% increased risk of MS [238]. No elevated risk was seen for individuals who reported physical or sexual abuse during childhood or adolescence in the study by Riise et al [239].…”
Section: Psychological Stressmentioning
confidence: 99%
“…Stressful life circumstances might explain the timing of symptom exacerbation for some patients with MS, perhaps by perturbing an already unstable neuroimmunological system [237]. Sickness, accidents or death of a family member and major changes to a romantic or working relationship posed a 14% to 26% increased risk of MS [238]. No elevated risk was seen for individuals who reported physical or sexual abuse during childhood or adolescence in the study by Riise et al [239].…”
Section: Psychological Stressmentioning
confidence: 99%
“…Previous studies on adverse events have mainly focused on adulthood and have found that most events happened during the last 1–5 years before MS onset. 3 32 33 …”
Section: Discussionmentioning
confidence: 99%
“…This is the first fully prospective study that has assessed the association between childhood adverse events and subsequent MS. Previous studies on adverse events have mainly focused on adulthood and have found that most events happened during the last 1–5 years before MS onset 3 32 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim was to explore the direction of the associations. As women with future MS did not have the vulnerability of having a chronic condition [ 6 , 8 ], higher rates of abuse in this group could signify that adult abuse predating the diagnosis could be risk or trigger factor for MS [ 24 , 25 ], or associated with unknown confounders, rather than being a consequence of MS. In this analysis, we excluded women who had their first symptom of MS within 5 years after MoBa inclusion and could have been in a prodromal phase of MS [ 26 ].…”
Section: Methodsmentioning
confidence: 99%